The Improvement of Reading Comprehension Ability in Explanation Text with PORPE Strategy - Wati, Endar; Suhardi, Suhardi (Universitas Pendidikan Ganesha, 2022)
Reading skills have an important role in the process of acquiring knowledge and information. Understanding a discourse is a form of obtaining complete and comprehensive information. This study aims to improve students' understanding ability in reading explanatory texts by using the PORPE learning strategy. This research is classroom action research conducted in two cycles. Subjects in this study amounted to 32 students. Data was collected using test and non-test methods. The instruments used were reading comprehension tests to measure students' reading comprehension skills, observation sheets to observe classroom conditions during learning, and questionnaires to collect data on students' perceptions of the PORPE learning strategy. The data that has been collected is then analyzed descriptively. The results showed that the PORPE learning strategy could improve the process of learning to read explanatory texts; the value of students' reading comprehension skills increased at the end of the cycle, and students gave positive responses to the use of the PORPE learning strategy in learning to read. Based on these findings, the PORPE learning strategy is recommended as an alternative to improve the quality of learning, especially in learning to read.